IMPLEMENTATION OF CHARACTER EDUCATION STRENGTHENING BASED ON LOCAL WISDOM IN SD LABORATORIUM UPI TASIKMALAYA - Riga Zahara Nurani; Hatma Heris Mahendra (PrimaryEdu : Journal of Primary Education, 2020)
This research is motivated by one of the government programs namely Strengthening Character Education (PPK), especially in elementary schools to produce a golden generation in 2045. The characters studied include 5 main characters namely religious, nationalist, integrity, independent, and mutual cooperation. This research will be conducted at the SD Laboratorium UPI Tasikmalaya. In addition to instilling character education in daily activities, in this school, there is also a love for local wisdom. The research method used is a descriptive qualitative method. Based on the results of the study, inculcation of character education based on local wisdom in the SD Laboratorium UPI Tasikmalaya was implemented through habituation and through classroom learning. The habituation is done not only in the classroom or in the school environment, but habituation also involves students' parents at home. In the learning process, the inculcation of character education based on local wisdom is applied by the teacher through learning materials, learning media, and also the evaluation of learning used. Planting character education is not enough to only be instilled in schools but there must be cooperation with parents of students at home.